Risk of Coronary Artery Disease in Patients With Traumatic Intracranial Hemorrhage: A Nationwide, Population-Based Cohort Study. Issue 50 (December 2015) - Lin, Wei-Shiang; Lin, Chin-Sheng; Liou, Jun-Ting; Lin, Wen-Yu; Lin, Cheng-Li; Cheng, Shu-Meng; Lin, I-Ching; Kao, Chia-Hung
Abstract : Abstract: Traumatic intracranial hemorrhage (ICH) is prevalent worldwide with long-term consequences, including disabilities. However, studies on the association of traumatic ICH with coronary artery disease (CAD) are scant. Therefore, this study explored the aforementioned association in a large-scale, population-based cohort. A total of 128, 997 patients with newly diagnosed traumatic ICH and 257, 994 age- and sex-matched patients without traumatic ICH from 2000 to 2010 were identified from Taiwan's National Health Insurance Research Database. The Kaplan–Meier method was used for measuring the cumulative incidence of CAD in each cohort. Cox proportional regression models were used for evaluating the risk of CAD in patients with and without traumatic ICH and for comparing the risk between the 2 cohorts. The Kaplan–Meier analysis revealed that the cumulative incidence curves of CAD were significantly higher in patients with traumatic ICH than in those without ICH (log-rank test, P  < 0.001). After adjustment for age, sex, and comorbidities, patients with traumatic ICH were associated with a higher risk of CAD compared with those without traumatic ICH (adjusted hazard ratio = 1.16, 95% confidence interval = 1.13–1.20). Compared with the general population, patients with traumatic ICH and having underlying comorbidities, including diabetes, hypertension, hyperlipidemia, chronic obstructive pulmonary disease, chronic kidney disease, and congestive heart failure, exhibited multiplicative risks of developing CAD. This cohort study revealed an increased risk of CAD in patients with traumatic ICH. Therefore, comprehensive evaluation and aggressive risk reduction for CAD are recommended in these patients.